Navigating special education relationships : building collective efficacy for a collaborative team - Ly, Amanda; Boll, Lori (London : Routledge, Taylor & Francis Group, 2024)
Told through a series of real-life stories and hard-learned lessons, Amanda Ly and Lori Boll share the challenges in special education relationships experienced through the lens of a special educator, a parent of a son with profound disabilities, and a child psychologist. Ideally, teachers, therapists, and parents working with students with special needs should form a cohesive team. However, these three parties often function as separate entities with different goals and objectives. Over the past 25 years, the authors have observed a consistent pattern of miscommunication and overlooking the importance of the mental and physical well-being of each team member, which contributed to poor collaboration. This book takes readers on a journey through the process of discovering whether you have, or are working with, a student with special needs; navigating how to best work with the student and other members of the team; and lastly, discussing ways to empower the reader and all members of the team. The authors posit that if we understand one another's perspectives, learn how to communicate more effectively, and focus on self-care, we will increase Collective Efficacy and become the collaborative team our students need us to be. As the first book to connect the concept of Collective Efficacy to special education, this is a must-read for teachers, therapists, and parents aiming to grasp the complexities of relationships in special education teams and better understand how mental health influences the effectiveness of each individualś role.
Keywords: Special education; EDUCATION / Special Education / Learning Disabled; EDUCATION / Special Education / General; EDUCATION / Teaching Methods & Materials / General